ANALISIS BAURAN PROMOSI OBJEK WISATA UNTUK MENINGKATKAN JUMLAH KUNJUNGAN KE PEMANDIAN MATO AIA NAGARI PANINGGAHAN KEC. JUNJUNG SIRIH KAB. SOLOK, SUMATRA BARAT - Nadilla Permata Putri; Rusydi Fauzan (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
The Mato Aia Baths in Paninggahan Village have experienced significant growth over the years. During the 18 years since the baths opened, the majority of visitors were from the surrounding community during the first phase. In the second phase, when it opened to the public, facilities at the baths were expanded, including food and beverage stalls, restrooms, a larger prayer room, and a parking area. During the third phase, the parking area was expanded to accommodate more vehicles and changing rooms were added to enhance visitor comfort. This study aims to analyze the promotional mix strategies implemented by the management of the Mato Aia Baths tourist attraction and their effectiveness in attracting tourists. The study  used qualitative methods with a descriptive approach. Data collection techniques included interviews, observations, and documentation with managers, youth, the community, and visitors. The results showed that out of 130 responses, 12 (9.2%) stated that the promotional performance was "Good." A total of 71 responses (54.6%) stated that promotional performance was in the "Moderate" category, and 47 responses (36.2%) stated that promotional performance was in the "Poor" category. The majority of promotional performance fell into the "Moderate" category (54.6%), indicating that promotional activities at Mato Aia Hot Springs were not optimal. This indicates that promotional performance still needs to be improved to achieve more optimal results.